CIMT 2018: Pushing frontiers in cancer immunotherapy - Report on the 16th Annual Meeting of the Association for Cancer Immunotherapy - Jan Beck; Matthias Birtel; Daniel Reidenbach; Nadja Salomon; Mustafa Diken (Taylor & Francis Group, 2018)
The 16th Annual Meeting of the Association for Cancer Immunotherapy (CIMT), Europe's largest meeting series of its kind, took place in Mainz, Germany from 15-17 May, 2018. Cutting-edge advancements in cancer immunotherapy were discussed among more than 700 scientists under the motto "Pushing Frontiers in Cancer Immunotherapy". This meeting report is a summary of some of the CIMT 2018 highlights.